The effect of Wordwall gamification on students’ motivation and critical thinking in ratio material - Sri Margiyati; Dini Rakhmawati; Ngatmini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
This study aims to examine the effect of Wordwall gamification on the learning motivation and critical thinking skills of sixth-grade elementary school students in ratio material. A quantitative quasi-experimental design with nonequivalent control group was used. The sample consisted of 50 students selected through purposive sampling, divided into experimental and control groups. Data were collected using a motivation questionnaire and HOTS-based critical thinking test, then analyzed using MANOVA. Results indicate that Wordwall significantly improves both learning motivation and critical thinking skills, both partially and simultaneously. Wordwall media showed a significant positive effect on both variables. For learning motivation, the significance value was p < 0.05 with an effect size of 84.9%. For critical thinking skills, the significance value was also p < 0.05 with an effect size of 64.7%. Pillai's Trace value = 0.864; F(2,47) = 149.672; p < 0.001. This means the combination of dependent variables differs significantly across classes. This finding suggests that Wordwall can serve as an effective, engaging, and practical alternative media to enhance mathematics learning quality in elementary schools.